2020
DOI: 10.1007/s11156-020-00902-z
|View full text |Cite
|
Sign up to set email alerts
|

Earnings forecasts: the case for combining analysts’ estimates with a cross-sectional model

Abstract: We propose a novel method to forecast corporate earnings, which combines the accuracy of analysts' forecasts with the unbiasedness of a cross-sectional model. We build on recent insights from the earnings forecasts literature to improve analysts' forecasts in two ways: reducing their sluggishness with respect to information in recent stock price movements and improving their long-term performance. Our model outperforms the most popular methods from the literature in terms of forecast accuracy, bias, and earnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Jog and McConomy, 2003;Shi et al, 2008;B edard et al, 2016) found that the degree of underpricing fell when anticipated profits were disclosed in IPO prospectuses. A recent study by Azevedo et al (2021) offers new insights regarding constructing models for profit estimates when analysing stock price volatility and long-term performance. Such an innovative strategy for forecasting earnings significantly enhances stock price accuracy.…”
Section: Related Literature and Hypothesis Development 21 Earnings Fo...mentioning
confidence: 99%
“…Jog and McConomy, 2003;Shi et al, 2008;B edard et al, 2016) found that the degree of underpricing fell when anticipated profits were disclosed in IPO prospectuses. A recent study by Azevedo et al (2021) offers new insights regarding constructing models for profit estimates when analysing stock price volatility and long-term performance. Such an innovative strategy for forecasting earnings significantly enhances stock price accuracy.…”
Section: Related Literature and Hypothesis Development 21 Earnings Fo...mentioning
confidence: 99%
“…Both models outperform the previous HVZ model. Azevedo et al (2021) have proposed a method to forecast corporate earnings [14] by employing a parsimonious cross-sectional regression model consisting of analyst forecasts of earnings, gross profits, and past stock performance, leading to a more accurate and less biased result.…”
Section: -Introductionmentioning
confidence: 99%
“…Recently, earnings forecasts based on a cross-sectional model, which only requires firms' fundamental features such as accounting numbers, have emerged as an alternative method (Hou, van Dijk, & Zhang, 2012: hereafter HVZ). This method is widely applied to exploring the mean reversion characteristics of earnings (Fama & French, 2000), estimating the implied cost of capital (HVZ; Li & Mohanram, 2014), detecting market overreactions to analyst forecasts (So, 2013), and improving forecasts in connection with the differential persistence of earnings components (Call, Hewitt, Shevlin, & Yohn, 2016) or past analyst forecasts (Azevedo, Bielstein, & Gerhart, 2020).…”
Section: Introductionmentioning
confidence: 99%